(untitled) (Communication & Society, 2000)
The close relationship between creative and technical process in Photography has been considered as an important fact in renewing the traditional knowledge of the art. From this point of view, recent historiography takes for granted that Photography has broken the limits of those subjects which are considered as artistic and has broadened the range to include everything stemming from modern visual culture related to the Media. It has been supposed that Photography had opened a “democratic” era of the art (both from the point of view of consume and creation), where chance and automatism creative have the highest importance, to the detriment of personal inspiration, which the fact of Benjamin´s theory of “aura” considers to be an aristocratic remain of the times before the Vanguards. This article proposes that this approach is not only untrue historically but that it is also far from describing the present situation of modern art. Like at the beginning of photography, when mechanical deed was an obstacle for the artistic recognition of the new invention, artistic photography is nowadays exhibited in galleries and museums, rather than the places which theoretically were supposed to be its natural medium of showing: the Media. The Boris Groys´ ideas about the new aristocratic vision of contemporary photographers support the need to revise what is considered artistic in Photography.